The Development of Sustainable Fashion: A Bibliometric Analysis Study - Rosa Amelia; Wulansari Prasetyaningtyas (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
The development of sustainability issues in the fashion industry has increased academic attention to sustainable fashion. This study aims to analyze (1) research trends, (2) author productivity and collaboration, (3) state productivity, (4) keyword development, (5) productivity of scientific journals globally. The method used was a quantitative bibliometric analysis of 251 Scopus indexed articles for the 2016-2025 period, with indicators of annual publications, state contributions, author collaboration networks, keyword frequency, and journal distribution. The dataset is limited to journal articles, open access, English, in the social sciences group, so that the findings are interpreted according to the scope. The results show a significant increase in publications from 2 articles in 2016 to 72 articles in 2025. Publications are dominated by the United Kingdom and the United States, while China and South Korea stand out in productivity and international collaboration. Author analysis identifies key authors with intense collaboration. The keywords sustainable fashion and sustainability dominate, reflecting a shift towards a more applicative and multidimensional approach. The novelty of this study lies in the comprehensive mapping of sustainable fashion trends for a decade (2016-2025) based on Scopus with the PRISMA approach and VOSviewer visualization. Overall, sustainable fashion is developing as a dynamic, collaborative, and strategic field of study in responding to the sustainable challenges of the global fashion industry.